Computation of Information Hiding Capacity and E-Capacity Lower Bounds - Tonoyan, Smbat A . (Mathematical Problems of Computer Science, 2021)
The binaryHamming case of the E-capacity and capacity results for information hiding system [1, 2] is evaluated for practical interests. A special parallel algorithm is elaborated and the computational software utilities are developed. The graphs, describing dependences of information hiding rate from the reliability and allowed distortion levels for the information hider and the attacker are obtained and presented. Also the graphical view of the capacity, depending from the allowed distortion levels is plotted.